Detection of Primary Sites in Cervical Lymphnode Metastases (Bangladesh Journal of Otorhinolaryngology, 2025)
Background: A common denominator to all malignancy is their ability to metastasize. Some tumours have the propensity to extensive local invasion without metastasis, whereas others metastasize early on in their development. With the exception of distant metastasis, the presence of cervical lymph node metastasis is the single most adverse independent prognostic factor in head and neck squamous cell carcinoma.Methods: This was a cross sectional study. Sixty (60) patients were studied in Department of Otolaryngology-Head & Neck Surgery, Combined Military Hospital, Dhaka, from July 2021 to June 2022. The study expected to show different types of head & neck cancer metastasizing to cervical lymph nodes, the age & sex distribution & clinical presentation of metastatic neck node.Results: Incidence of carcinoma pyriform fossa was seen in 9 (15%) cases, 4 (6.67%) cases of metastatic neck node were seen to take origin from nasopharynx, 3 (5%) cases from base of the tongue, and 2 (03.33%) cases from buccal mucosa, 1 (1.67%) case from sinonasal, 1 (1.67%) from oral tongue & 1 (1 .67) case from tonsil. Among the non-squamous origin 8 (15.09%) cases were found to arise from Ca-thyroid of which 7 were papillary thyroid carcinoma and 1 was follicular thyroid carcinoma. 2 (3.77) cases from Ca-parotid of which 1 was adenoid cystic carcinoma and 1 was mucoepidermoid carcinoma.Conclusion: All the data presented in this study may considerably vary with any large series though inflammatory neck disease is very common in our country, one should not forget the possibility of metastatic carcinoma While enlarged cervical node in an elderly patient should always be considered as metastatic until proved otherwise.Bangladesh J Otorhinolaryngology 2024; 30 (2): 76-83